MOTION GRAPHIC PROMOSI PASAR PAPRINGAN DI TEMANGGUNG, JAWA TENGAH - Resty Fauzyah; Elda Franzia (Jurnal Dimensi DKV Seni Rupa dan Desain, 2018)
AbstractMotion Graphic of Papringan Market Promotion at Temanggung, Central Java. Motion graphic is an infographic designed to move like audio-visual media in the form of film, video and animation in computer. Motion graphic promotion for Papringan Market is one of many steps to promote Papringan Market. Papringan Market is a unique tourist  place held under the bamboo plants. Some visual elements of design found in motiongraphics can give influence to audience. The visual elements of the design used in motion graphics should be in accordance with their usability and function. So for that researchers will analyze about Motion Graphic Papringan Market promotion to determine whether the visual elements of the design used is appropriate according to its usefulness andfunction or not. To answer the problem of the research, the researcher uses the research type of qualitative observation method to be able to know, understand, deeply examine, and expose it in writing about all visual elements contained in the motion graphic, from video, film, typography, illustration, photography and music. Based on the results ofresearch that has been done, motion graphic promotion for Papringan Market still had many visual elements that have to be repaired, because still using visual elements that have not exactly usability or function. AbstrakMotion Graphic Promosi Pasar Papringan di Temanggung, Jawa Tengah. Motion graphic merupakan infografis yang didesain bergerak seperti media audio visual berupa film, video dan animasi dalam komputer. Motion graphic promosi Pasar Papringan merupakan salah satu langkah untuk mempromosikan Pasar Papringan. Pasar Papringan adalah tempat wisata unik yang digelar di bawah rimbunnya tanaman bambu. Beberapaelemen visual desain yang terdapat pada motion graphic dapat  memberikan pengaruh kepada penonton. Elemen visual desain yang digunakan pada motion graphic harus sesuai dengan kegunaan dan fungsinya. Maka untuk itu peneliti akan menganalisis tentang motion graphic promosi Pasar Papringan untuk mengetahui apakah elemen visualdesain yang digunakan sudah tepat sesuai kegunaan dan fungsinya atau belum. Untuk menjawab permasalahan dalam penelitian, peneliti menggunakan jenis penelitian metode observasi kualitatif untuk dapat mengetahui, memahami, mengkaji secara mendalam, dan memaparkannya dalam tulisan mengenai semua elemen visual yang terdapat di dalam motion graphic tersebut, mulai dari video, film, tipografi, ilustrasi, fotografi, dan musik. Berdasarkan hasil penelitian yang telah dilakukan motion graphic promosi Pasar Papringan masih banyak elemen-elemen visual yang masih harus diperbaiki, karena masihmenggunakan elemen-elemen visual yang belum tepat kegunaan atau fungsinya.